2013 update in nephrology - de Seigneux, Sophie; Saudan, Patrick (Revue médicale suisse, 2014)
Vasopressin antagonists show for the first time a beneficial effect on ADPKD cyst growth and renal function in a large cohort of patients. In ANCA vasculitis, the 18 months follow-up of Rituximab treatment for induction confirms the safety and efficacy of this therapeutic option. Two studies brought some answers to what is the more appropriate intravenous fluid strategy to decrease the incidence of acute kidney injury in critically ill patients. Regarding mortality in dialysed patients, inconclusive results about the use of calcimimetics to decrease cardiovascular mortality have been reported but there is good evidence that hemodiafiltration with high ultrafiltration volume can decrease significantly the mortality in these